Brachytherapy training survey among radiation oncology residents in Europe. (December 2022) - Sturdza, Alina Emiliana; Stephanides, Marianne; Jurgenliemk-Schulz, Ina; Eriksen, Jesper Grau; Benstead, Kim; Hoskin, Peter; Vlad, Stefanel; Escande, Alexandre; Corradini, Stefanie; Knoth, Johannes; Westerveld, Henrike; Tagliaferri, Luca; et al.
Highlights: Educating new generations of radiation oncologist specialized in brachytherapy is important. A survey investigating the current status of training among the residents shows interest in brachytherapy, but lack of confidence in starting a practice. Access to mentors and high case load exposure during training are essential. A formal and comprehensive logbook and BT curriculum need to be developed. Abstract: We aim to investigate the current state of brachytherapy (BT) training among the radiation oncology trainees in Europe. Material and methods: A 22-question online survey based on the one by the American Association of Radiation Oncology Residents (2017) with added queries pertinent to training in Europe was sent to 1450 residents in two iterations. These included site-specific training, volume of experience, barriers to training, institutional support, and preferences for further education. Responses to individual statements were given on a 1 to 5 Likert-type scale. The answers were reported by junior (≤3 years of training) and senior years of training (year of training 4/5/6 and junior staff). Descriptive statistics were used to describe frequencies. Results: Residents from 21 European countries participated, 445 (31%) responded. 205 (47%) were senior residents. 60% residents consider that performing BT independently at the end of residency is very or somewhat important. Confidence in joining a brachytherapy practice at the end of residency was high or somewhat high in 34% of senior residents. They reported as barriers to achieving independence in BT to be lack of appropriate didactic/procedural training from supervisors (47%) and decreased case load (31%). 68% reported their program lacks a formal BT curriculum and standardized training assessment. Conclusions: Residents in Europe, feel independent BT practice is very or somewhat important, but do not feel confident they will achieve this goal. To address this gap, efforts are needed to develop and implement a formal and comprehensive BT curriculum with easy access to trained instructors.